Photo-switchable tweezers illuminate pore-opening motions of an ATP-gated P2X ion channel - Habermacher, Chloé; Martz, Adeline; Calimet, Nicolas; Lemoine, Damien; Peverini, Laurie; Specht, Alexandre; Cecchini, Marco; Grutter, Thomas (eLife, 2016)
P2X receptors function by opening a transmembrane pore in response to extracellular ATP. Recent crystal structures solved in apo and ATP-bound states revealed molecular motions of the extracellular domain following agonist binding. However, the mechanism of pore opening still remains controversial. Here we use photo-switchable cross-linkers as ‘molecular tweezers’ to monitor a series of inter-residue distances in the transmembrane domain of the P2X2 receptor during activation. These experimentally based structural constraints combined with computational studies provide high-resolution models of the channel in the open and closed states. We show that the extent of the outer pore expansion is significantly reduced compared to the ATP-bound structure. Our data further reveal that the inner and outer ends of adjacent pore-lining helices come closer during opening, likely through a hinge-bending motion. These results provide new insight into the gating mechanism of P2X receptors and establish a versatile strategy applicable to other membrane proteins.
Keywords: P2X receptors; azobenzene photoswitch; gating mechanism